A new BlueGreen methodology for designing next generation networks. (1st January 2012) - Liu, William; Sirisena, Harsha; Pawlikowski, Krzysztof
In this paper, we propose a BlueGreen methodology to rethinking and redesigning network protocols, so as to satisfy the criteria of being service and energy efficiencies. The next generation networks (NGNs) are required to satisfy both extremely high levels of service resilience by the overprovision of redundant network resources (i.e., Blue criteria), and also minimising consumption of energy by switching off unnecessary network resources (i.e., Green criteria). Thus, there is an inherent contradiction involved in satisfying both these perspectives simultaneously. In effect these represent an optimisation problem, where the network elements and their energy consumption are considered as a resource and their utilisation should be minimised. The impact of turning off any nodes or links which might lead to disintegration of a given network topology are also studied. The case studies presented confirm that the BlueGreen approach shows promise for integrating service and energy efficiencies to achieve specified BlueGreen targets.